2020
DOI: 10.1159/000506186
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Enterocolitis in a Patient with Refractory Immune-Related Colitis

Abstract: Although most immune-related adverse events (irAEs) secondary to immune checkpoint inhibitors can be managed with immunosuppressive therapies; they can induce reactivation of infectious diseases, including cytomegalovirus (CMV). Here, we show a case of CMV enterocolitis during steroid therapy for an irAE. A 77-year-old man with unresectable malignant melanoma was treated with ipilimumab. He suffered from immune-related colitis (irColitis) and was treated with methylprednisolone. Although corticosteroids initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…CMV, EBV and VZV are herpesviruses that establish a state of chronic latent infection in most humans by adulthood. 84 While there are a number of reports of CMV following immunosuppression, [36][37][38] reactivation of CMV, 85 86 EBV 87 and VZV 88 89 in the absence of immunosuppression has also been reported, with features mimicking irAEs. 90 In fact, some evidence suggests CMV may actually be an underlying trigger for severe irAEs, as CMV is found disproportionately among severe ICI-associated pneumonitis and colitis.…”
Section: Human Herpesviridae: CMV Varicella-zoster Virus (Vzv) and Epstein-barr Virus (Ebv)mentioning
confidence: 99%
“…CMV, EBV and VZV are herpesviruses that establish a state of chronic latent infection in most humans by adulthood. 84 While there are a number of reports of CMV following immunosuppression, [36][37][38] reactivation of CMV, 85 86 EBV 87 and VZV 88 89 in the absence of immunosuppression has also been reported, with features mimicking irAEs. 90 In fact, some evidence suggests CMV may actually be an underlying trigger for severe irAEs, as CMV is found disproportionately among severe ICI-associated pneumonitis and colitis.…”
Section: Human Herpesviridae: CMV Varicella-zoster Virus (Vzv) and Epstein-barr Virus (Ebv)mentioning
confidence: 99%
“…Although symptoms of organ inflammation after exposure to ICI are often attributed to irAEs, CMV must remain among the differential diagnoses for these patients. Misdiagnosis of CMV infection and off-target management for presumed irAEs due to overlapping symptoms could lead to unfavorable outcomes [ 13 , 18 , 19 ]. This study represents the largest sample analysis examining the incidence and characteristics of CMV infection in the ICI-treated patient population.…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective analysis found a strong association between ICI-related pneumonitis and pulmonary CMV infection and suggested that ICI pneumonitis may have a component of an immune reconstitution syndrome associated with CMV pneumonitis [ 24 ]. In addition, several case reports have shown GI CMV infection to be associated with immune-mediated diarrhea and colitis (IMDC) refractory to therapy [ 17 , 18 , 25 ]. The proposed mechanism for this is that steroid treatment for irAEs lowers T-cell–mediated immunity and therefore increases the chances of CMV infection [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With great interest we read the case report by Furuta et al [ 1 ] concerning cytomegalovirus (CMV) as cause of continuing enterocolitis in a patient with immune checkpoint inhibition-related colitis (ICIRC). The authors describe a patient with steroid-refractory ulcerative colitis after treatment with nivolumab and ipilimumab.…”
mentioning
confidence: 99%